STAR-ANISE EXTRICATE BENEFITS - Mohamad, Prof. Jakir; Sheikh, Prof. Sanad (International Journal of Multidisciplinary Research and Studies, 2021)
Illicium verum has long been utilized in conventional medicinal drug and meals enterprise to save from cold and relieves pain. Sometimes its miles are infected with the tremendously poisonous Japanese star anise (Illicium anisatum L.). Contains toxic sesquiterpenes the conventional utilization of Illicium verum is documented from South and West Asia in which it's used and consumed for plenty of obstacles. Several bioactive components along with sesquiterpenes, phenylpropanoids, lignans, flavonoids, and different compounds are identified through Illecium verum. The activity of pharmacological research is compounds have a wide range of pharmacological uses, especially cytotoxicity, antioxidants, anti-inflammatory agents, sedatives, and sedatives. Antibacterial action. It is also the main source of anti-cancer drugs (shikimic acid). The modern-day evaluation is facts on botany, traditional usage, phytochemistry and pharmacology, and the toxicology of illicium anisatum verum.